Let the side of the regular hexagon be a.
Calculating a
b = 180-60-45
b = 75°
(c/sin75) = (2/sin45)
c = (1+√(3)) units.
d² = 2a²-2a²cos120
d = √(3a²)
d = √(3)a ----- (1).
e = c+a, and c = (1+√(3)) units.
e = (1+√(3)+a) --- (2).
Therefore equating (1) and (2).
√(3)a = 1+√(3)+a
√(3)a-a = √(3)+1
a(√(3)-1) = √(3)+1
a = (√(3+1)/(√(3)-1)
a = (√(3)+2) units.
It implies;
The required length is;
a-2
Where a is the side length of the regular hexagon, (√(3)+2) units.
= √(3)+2-2
= √(3) units.
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support